2022
DOI: 10.3390/foods11162439
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant and Anti-Inflammatory Effects of Flavonoids from Propolis via Nrf2 and NF-κB Pathways

Abstract: Accumulating evidence shows that oxidative stress and inflammation contribute to the development of cardiovascular disease. It has been suggested that propolis possesses antioxidant and anti-inflammatory activities. In this study, the antioxidant and anti-inflammatory effects of the main flavonoids of propolis (chrysin, pinocembrin, galangin, and pinobanksin) and propolis extract were researched. The results showed that the cellular ROS (Reactive oxygen species) levels, antioxidant enzymes, Nrf2 (Nuclear facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 62 publications
0
21
0
1
Order By: Relevance
“…Reactive oxygen species (ROS) are associated with NF-κB signaling and play a critical role in the anti-inflammatory effects of several functional foods rich in isoflavonoids [ 38 , 39 , 40 ]. Narirutin, a key flavonoid of Citrus junos , was reported to have an anti-inflammatory effect on lipopolysaccharide-stimulated macrophages by lowering IL-β, TNF-α, nitric oxide (NO), and prostaglandin E2 through the inhibition of NF-κB and MAPKs activation in vitro [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are associated with NF-κB signaling and play a critical role in the anti-inflammatory effects of several functional foods rich in isoflavonoids [ 38 , 39 , 40 ]. Narirutin, a key flavonoid of Citrus junos , was reported to have an anti-inflammatory effect on lipopolysaccharide-stimulated macrophages by lowering IL-β, TNF-α, nitric oxide (NO), and prostaglandin E2 through the inhibition of NF-κB and MAPKs activation in vitro [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that apigenin and genistein may interact with the IκBα/NF-κB complex with the binding energies of −34.0 and −31.7 kJ/mol, respectively, leading to decreased IκBα and p65 phosphorylation, attenuated NF-κB nuclear translocation, and inactivated NF-κB signaling ( 146 ). Similarly, quercetin, chrysin, pinocembrin, galangin, pinobanksin, and nobiletin can suppress NF-κB signaling by inhibiting IκBα and p65 phosphorylation and suppressing NF-κB nuclear translocation ( 147 149 ). Both cajanin (3’,5-dihydroxy-7-methoxy-isoflavone) and prunetin (5-hydroxy-7-methoxy-isoflavone) may inhibit IκBα and p65 phosphorylation.…”
Section: Natural Flavonoids Exhibit Protective Activity Against Oa De...mentioning
confidence: 99%
“…Studies on propolis have shown that flavonoids belonging to propolis exhibited strong antioxidant properties [3,20,23–27] . It has been proven that these flavonoids inhibit the oxidation of lipoproteins by inhibiting copper ions [28] .…”
Section: Introductionmentioning
confidence: 99%